INCREASING LEARNING INTEREST AND SOCIAL SKILLS OF CLASS III STUDENTS THROUGH SOCIODRAMA LEARNING METHODS - Mufidatun Nisa'; Triana Tasha Mahardhiella; Alya Khoirun Nisa'; Ana Naimatul Jannah (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This study aims to determine the use of the sociodrama method in increasing class III students' interest in learning and social skills in Civics subjects at UPTD SDN Demangan 1. This research is a classroom action research with the design proposed by Kemmis and Mc Taggart which is a developmental model of Kurt's model. lewin. The data obtained in this study were by means of observation data collection techniques, interviews, and distributing questionnaires to students. Data analysis techniques used are qualitative and quantitative. In this study, the results were obtained that prior to the sociodrama learning method, students' interest in learning and social skills were still low. So that researchers seek learning that is more fun and involves students directly. After the sociodrama learning method was used, students' interest in learning and social skills possessed by students could increase. So that the results obtained in the first cycle were 56% and in the second cycle the results were obtained 87%, which means that the implementation of this action has increased 31%. Thus, this result has reached the target of success. After this research, it is hoped that teachers can continue to apply the sociodrama method but also continue to develop more fun learning methods.